Where do firms' recombinant capabilities come from? Intraorganizational networks, knowledge, and firms' ability to innovate through technological recombination - Carnabuci, Gianluca; Operti, Elisa (Strategic Management Journal, 2013)
A firm's innovativeness is driven by its ability to recombine existing technologies. Elaborating on this argument, we contend that there exist two distinct types of recombinant capabilities. First, firms may innovate through recombinant creation, i.e., by creating technological combinations new to the firm. Second, they may innovate through recombinant reuse; i.e., by reconfiguring combinations already known to the firm. We study what drives each type of capability by examining two factors: the degree of integration of a firm's intraorganizational network and the diversity of its knowledge base. We test our theoretical predictions using data on 126 semiconductor firms between 1984 and 2003. Our analyses indicate that factors that favor recombinant creation generally hinder recombinant reuse and vice versa; however, combining an integrated collaboration network and a diverse knowledge base may concurrently enhance both recombinant capabilities . Copyright © 2013 John Wiley & Sons, Ltd.